Docosahexaenoic acid‐supplementation prior to fasting prevents muscle atrophy in mice. Issue 5 (15th February 2016) - Deval, Christiane; Capel, Frédéric; Laillet, Brigitte; Polge, Cécile; Béchet, Daniel; Taillandier, Daniel; Attaix, Didier; Combaret, Lydie
Abstract: Background: Muscle wasting prevails in numerous diseases (e.g. diabetes, cardiovascular and kidney diseases, COPD, …) and increases healthcare costs. A major clinical issue is to devise new strategies preventing muscle wasting. We hypothesized that 8‐week docosahexaenoic acid (DHA) supplementation prior to fasting may preserve muscle mass in vivo . Methods: Six‐week‐old C57BL/6 mice were fed a DHA‐enriched or a control diet for 8 weeks and then fasted for 48 h. Results: Feeding mice a DHA‐enriched diet prior to fasting elevated muscle glycogen contents, reduced muscle wasting, blocked the 55% decrease in Akt phosphorylation, and reduced by 30–40% the activation of AMPK, ubiquitination, or autophagy. The DHA‐enriched diet fully abolished the fasting induced‐messenger RNA (mRNA) over‐expression of the endocannabinoid receptor‐1. Finally, DHA prevented or modulated the fasting‐dependent increase in muscle mRNA levels for Rab18, PLD1, and perilipins, which determine the formation and fate of lipid droplets, in parallel with muscle sparing. Conclusions: These data suggest that 8‐week DHA supplementation increased energy stores that can be efficiently mobilized, and thus preserved muscle mass in response to fasting through the regulation of Akt‐ and AMPK‐dependent signalling pathways for reducing proteolysis activation. Whether a nutritional strategy aiming at increasing energy status may shorten recovery periods in clinical settings remains to be tested.